2011
DOI: 10.1073/pnas.1015948108
|View full text |Cite
|
Sign up to set email alerts
|

Late Carboniferous paleoichnology reveals the oldest full-body impression of a flying insect

Abstract: Insects were the first animals to evolve powered flight and did so perhaps 90 million years before the first flight among vertebrates. However, the earliest fossil record of flying insect lineages (Pterygota) is poor, with scant indirect evidence from the Devonian and a nearly complete dearth of material from the Early Carboniferous. By the Late Carboniferous a diversity of flying lineages is known, mostly from isolated wings but without true insights into the paleoethology of these taxa. Here, we report evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 15 publications
1
38
1
Order By: Relevance
“…Molting temperature was taken as the temperature at the lowest measurement of the deficit phase. earth (Knecht et al 2011), and can molt up to 52 times as larvae (Gros 1925), whereas 4 to 5 larval molts are typical in more contemporary lineages (Benke and Wallace 1980). Whether molting number or frequency play a role in determining the susceptibility of species to thermal change or other environmental stressors is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Molting temperature was taken as the temperature at the lowest measurement of the deficit phase. earth (Knecht et al 2011), and can molt up to 52 times as larvae (Gros 1925), whereas 4 to 5 larval molts are typical in more contemporary lineages (Benke and Wallace 1980). Whether molting number or frequency play a role in determining the susceptibility of species to thermal change or other environmental stressors is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…This reinterpretation is based on published images and text in the original report (Knecht et al 2011), and a high‐resolution unpublished photograph of the fossil. No features of the fossil were considered beyond what was presented in the original report.…”
Section: Methodsmentioning
confidence: 99%
“…Winged insects (Pterygota) diverged and radiated during the Carboniferous (360–300 mya), yet insect fossils from that period are sparse and consist primarily of wings or wing fragments (Grimaldi and Engel 2005). A remarkably detailed full‐body imprint fossil of a pterygote insect was recently discovered from the Late Carboniferous (Knecht et al 2011) and provides rare information about morphology, habitat, and behavior, but correct interpretation of the imprint features and its maker's taxonomic identity are critical. Knecht et al concluded that the imprint was most likely produced by a lineage that gave rise to mayflies (Ephemeropterida).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It would not be unexpected for stem-group Euglossini to potentially reside outside of the area of distribution of modern orchid bees, perhaps even far afield as has been discovered in the pattern of biogeography for other corbiculate tribes (e.g., Kotthoff et al, 2013). In addition, euglossine fossils have the potential to preserve direct or indirect evidence of paleobiologies and behaviors, illuminating the early evolution of complex behavioral suites (e.g., Engel, 2009c;Chaboo et al, 2009;Wedmann et al, 2009;Davis & Engel, 2010;Wang et al, 2010;Batelka et al, 2011;Knecht et al, 2011;Gu et al, 2012;Pérez-de la Fuente et al, 2012;Huang et al, 2012Huang et al, , 2013Krogmann et al, 2013;Wappler et al, 2013). Evolving techniques of study and a greater appreciation of fossils will ultimately provide broader avenues for unraveling the origins of the charismatic Euglossini and their intimate relationship with orchids.…”
Section: Discussionmentioning
confidence: 99%